2022
DOI: 10.1186/s12944-022-01735-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the TyG index and rheumatoid factor for cardiovascular disease risk in a rheumatoid arthritis population: data from a survey of 418 patients

Abstract: Objective To investigate the correlation between the triglyceride-glucose (TyG) index and rheumatoid factor levels and the existence of cardiovascular disease in patients in the rheumatoid arthritis population and to analyze their potential value in predicting the risk of cardiovascular disease. Methods Patients with rheumatoid arthritis treated by the Traditional Chinese Medicine Department of Rheumatism of the China-Japan Friendship Hospital from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Multiple studies have shown that compared to the healthy control group, RF/ACCP-positive patients have a higher risk of cardiovascular events (including carotid intima-media thickness (cIMT), ischemic heart disease, atherosclerosis, etc.) (172,174,175). However, a study targeting 160,000 postmenopausal women with RA indicated that CVD risk is closely associated with CVD risk factors, severity of joint pain, and inflammation, but not related to being positive for anti-CCP or RF (176).…”
Section: The Impact Of Ra Autoantibodies On Blood Lipids and Cvd Riskmentioning
confidence: 99%
“…Multiple studies have shown that compared to the healthy control group, RF/ACCP-positive patients have a higher risk of cardiovascular events (including carotid intima-media thickness (cIMT), ischemic heart disease, atherosclerosis, etc.) (172,174,175). However, a study targeting 160,000 postmenopausal women with RA indicated that CVD risk is closely associated with CVD risk factors, severity of joint pain, and inflammation, but not related to being positive for anti-CCP or RF (176).…”
Section: The Impact Of Ra Autoantibodies On Blood Lipids and Cvd Riskmentioning
confidence: 99%
“…The pressing need for early detection methods in hepatic diseases remains unabated. Similarly, cardiovascular disorders present intricate challenges owing to their multifaceted nature 201,202 and the involvement of various causative factors 203–205 . Additionally, conventional pharmacological interventions often necessitate prolonged administration, which can inadvertently lead to drug resistance 206,207 and undesirable side effects 208 .…”
Section: Biomedical Applications Of Peptides and Pasmentioning
confidence: 99%
“…Similarly, cardiovascular disorders present intricate challenges owing to their multifaceted nature 201,202 and the involvement of various causative factors. [203][204][205] Additionally, conventional pharmacological interventions often necessitate prolonged administration, which can inadvertently lead to drug resistance 206,207 and undesirable side effects. 208 In light of these complexities, peptides/PAs, with their exceptional specificity, high affinity, and remarkable stability, have emerged as promising therapeutic modalities, providing novel insights and innovative approaches.…”
Section: Physical Modificationmentioning
confidence: 99%